Bringing introspection into BlobSeer: towards a self-adaptive distributed data management system - Carpen-Amarie, Alexandra; Costan, Alexandru; Cai, Jing; Antoniu, Gabriel; Boug'e, Luc (Zielona Góra: Uniwersytet Zielonogórski)
Introspection is the prerequisite of autonomic behavior, the first step towards performance improvement and resource usage optimization for large-scale distributed systems. In grid environments, the task of observing the application behavior is assigned to monitoring systems. However, most of them are designed to provide general resource information and do not consider specific information for higher-level services. More precisely, in the context of data-intensive applications, a specific introspection layer is required to collect data about the usage of storage resources, data access patterns, etc
Keywords: distributed systems; storage management; large-scale system; monitoring; introspection